A Play Of Performance Waktu Batu Yogyakarta Teater Garasi In The Dramaturgi Study - Nur Iswantara (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2021)
The title of the paper of Play of Performance Waktu Batu (WB) Yogyakarta Garasi Teater (TGY) in this Dramaturgy Study is a summary of research results at the Yogyakarta Institute of Indonesian (ISI) Research Institute in 2014. Research in dramaturgy studies uses the dramaturgy theory of George Kernodle & Portia Kernodle (1978 ). Kernodle states that in dramaturgy there are six possible dramatic values that can help arrange the unity of theater performances. The six dramatic values include plot, character, theme (structure), and dialogue, atmosphere and spectacles (texture). One of TGY’s inspirational works, namely the WB performances sourced from Javanese mythology: Watugunung, Murwakala, Sudamala and Late Majapahit History, became an aesthetic presentation especially “Waktu Batu” The Stories that Meet in the Ruang Tunggu’ (WB1) will be analyzed with a dramaturgy approach which includes structure: plot, character, theme, and texture: dialogue, atmosphere and spectacles. The results of analyzing the structure consisting of plots, characterizations and themes; texture: dialogue, mood and spectacle performance of WB 1, showing that TGY belongs to a theater group that positions as a ‘theater creation laboratory’ having a unique aesthetic concept, which is typical for building eclectic dramaturgy. The eclectic drama in the Indonesian contemporary theater scene, an TGY effort to create a WB 1 play originating from Javanese mythology: Sudamala, Murwakala, Watugunung and the late history of Majapahit so that it becomes an aesthetic presentation that can be enjoyed by the audience. TGY group can survive more than 20 years. In fact in Indonesia there are not many contemporary theater groups that can survive long enough. Every TGY staging is always in demand by the audience as the WB 1 play shows.